(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Asides direct gastrointestinal exposure, inhalation route is another major xenobiotic exposure pathway to the gastrointestinal tract via mucociliary escalator. This triphasic study assesses cement dust inhalatory exposure effect on the possible alterations of the gastrointestinal tissues and secretion. 72 male, sixteen (16) weeks old Wistar rats were randomized into 3 different phases of 24 animals. Each phase comprised of 3 group of 8 animals. Group 1 (control) were sham-operated with clean ambient air, group 2 (14-days exposed) were exposed to cement dust for 14days, and group 3 (28-day exposed) were exposed to cement dust for 28 days. Biochemical indices including superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), sulfhydryl group, carbonyl group, Na+-K+ATPase pump activity, Nitric oxide (NO) were investigated spectrophotometrically in gastric and hepatic tissues while histopathology was studied using standard procedure. There was significant increase in the level of MDA, NO and carbonyl- an observation that contrasts with the level of CAT, SOD and sulfhydryl; no significant difference in Na+-K+-ATPase pump was observed in the exposed groups compared with control. Histopathological alterations in salivary gland and gastric tissues includes edema, inflammatory cell infiltration and vascular congestion. There was significant alteration in basal salivary, gastric and biliary secretions; increased stimulated salivary and gastric secretion via cholinergic stimulation. Conclusively, histopathological and spectrophotometric analyses reflect that inhalatory experimental exposure to cement dust significantly alter gastrointestinal secretions and predisposes the gastrointestinal tract to an array of deleterious effects via protein oxidation and antioxidant depletion and tissue peroxidation.